Strategies, market orientation and capabilities: business performance perspectives from Pakistan, a developing market economy - Azhar, Sarwar Mehmood (2007)
The aim of this thesis is to study, in the context of a developing market economy, the relationship of Marketing Orientation, Strategic Orientation as well as marketing capabilities with business performance, individually as well as simultaneously and compare these with the proposed relationships suggested in the developed markets of the western world. The findings suggest that there is a strong relationship between these independent variables with performance but these are not always positive and in some cases not even significant. This in many areas contradicts the proposed positive influence of the above mentioned variables on business performance that is normally taken for granted in developed markets. This result is, however, in line with the results of a few studies carried out in the developing market context. For example a study by Usha and Haley (2006), notify that successful managers in their study argue that best practices developed for information-rich Western markets were not effective in information-void emerging markets.